Influence evaluation of UAV inlet on electromagnetic scattering and time-frequency characteristics. Issue 1 (July 2021) - Sun, Xumin
Abstract: An analytical method for electromagnetic scattering characteristics of complex unmanned aerial vehicle targets by using hybrid multilevel fast multipole algorithm (MLFMA)-physical optics (PO) and short-time fourier transformation (STFT) is proposed in this paper. By constructing accurate electromagnetic models of unmanned aerial vehicle (UAV) target with inlet, the aspect and polarization characteristics of radar cross section (RCS) and time-frequency representation (TFR) are studied. To validate the influence of the inlet, the monostatic and bistatic RCS at specific angles, RCS statistical characteristics and TFR correlation are simulated and compared. It is concluded that the inlet should be sufficiently considered to calculate the accurate scattering characteristics.